Changing racial boundaries and mixed unions: the case of second-generation Filipino Americans. Issue 14 (13th November 2016) - Gambol, Brenda
ABSTRACT: I examine an understudied topic of intermarriage – nonwhite mixed unions. Drawing on a study of second-generation Filipino Americans, I compare how respondents in inter-ethnic (those partnered with other Asians) and nonwhite interracial (i.e. Latino, black, and non-Asian bi-racial) unions perceive racial boundaries, or their 'racial schemas'. I argue that mixed unions can change how partners view racial boundaries. Drawing on phenotype, culture, and power position, both inter-ethnically and nonwhite interracially partnered respondents viewed themselves as different from whites. However, they differed in how they constructed nonwhite boundaries. Respondents in inter-ethnic unions drew on their Asian identity to distinguish themselves from Latinos and blacks, while informants in nonwhite interracial unions highlighted their Filipino identity to distance themselves from East Asians and align themselves with Latinos and blacks. These findings show that marriage affects racial boundary development and that mixed unions impact individuals' racial incorporation.